STABILITY ASSAY AND CONCENTRATION OPTIMIZATION OF MAGNESIUM CHLORIDE IN REACTION BUFFER AND DITHIOTHREITOL (DTT) IN STORAGE BUFFER FOR REVERSE TRANSCRIPTASE SIS7A FUSION - Valencia, Violeta
Reverse transcriptase (RT) is an enzyme with the ability to convert RNA chains into DNA chains, which is highly useful in molecular biology. To enhance the processivity and thermostability of RT, previous research involved engineering by fusing Sis7a with MMLV reverse transcriptase. However, to date, there has been no optimization of the reaction buffer or storage buffer for the Sis7a fusion RT. Therefore, this study aims to optimize the reaction and storage buffers for the Sis7a fusion RT to enhance its activity and stability. The tests were conducted using variations in the components of the reaction and storage buffers over three months, with storage temperatures set at -20°C, 4°C, and room temperature (~25°C). For the reaction buffer, variations were made with MgCl2 concentrations of 2.5 mM, 3 mM, and 3.5 mM, while for the storage buffer, variations were made with DTT concentrations of 2.5 mM, 5 mM, and 7.5 mM. The testing parameters included reverse transcription activity, which was measured based on the enzyme's ability to incorporate nucleotides in the formation of cDNA. The enzyme used in this study was produced on an 80 mL scale using a method optimized in previous research. Confirmation of the presence of the expression plasmid in the isolates was performed using PCR and electrophoresis targeting the T7 gene. Confirmation of protein results during harvesting, purification, and concentration processes was done using SDS-PAGE.The study found that the highest activity in the reaction buffer was with an MgCl2 concentration of 3 mM and in the storage buffer with a DTT concentration of 7.5 mM. Additionally, storage at -20°C provided the best activity results at various concentrations after three months. This research determined the optimum components for the reaction and storage buffers and the optimum storage temperature for the Sis7a fusion RT, supporting the application of this enzyme.